PENGARUH PEMBERIAN BEBERAPA KONSENTRASI EKSTRAK RUMPUT LAUT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) METODE SRI - Ramadhani, Hanadiya; Rozen, Nalwida; Sari, Afrima (Jurnal Agroteknologi, 2026)
Indonesia's high rice consumption, with a population of 284.4 million, stands in contrast to the national production levels in 2024. Based on data from that year, total annual rice production reached only approximately 29.80 million tons, which was insufficient to meet domestic demand. This shortfall occurred as paddy production in 2024 declined to 53.14 million tons (dry harvested grain), a 2.43% decrease compared to the 53.98 million tons produced in 2023. The environmentally friendly System of Rice Intensification (SRI) can enhance productivity by up to 50%. Indonesia's rich marine biodiversity, particularly seaweed, can serve as a biostimulant through extraction. Biostimulants contain compounds and microorganisms that enhance nutrient use efficiency in plants. This study aimed to evaluate the effects of seaweed extract concentrations on the growth and yield of rice and to assess its potential as a natural biostimulant for sustainable rice productivity, supporting organic farming. The study was conducted from June to October 2025 in rice fields at Koto Luar, Pauh, Padang. A Randomized Block Design (RBD) with one factor seaweed extract concentrations at 0%, 0.4%, 0.8%, 1.2%, and 1.6%. The data was analysed with analysis of variance at a 5% significance level and mean comparison of the Duncan’s New Multiple Range Test (DMRT) via STAR® (Statistical Tool for Agricultural Research). The research results showed that the seaweed extract at the 1.6% concentration was the best treatment effected of plant growth, yield components and crop yield of rice. The findings recommend increasing seaweed extract concentrations to enhance rice growth and yield.